A Plant like Cytochrome P450 Subfamily CYP710C1 Gene in Leishmania donovani Encodes Sterol C-22 Desaturase and its Over-expression Leads to Resistance to Amphotericin B - Bansal, Ruby; Sen, Shib Sankar; Muthuswami, Rohini; Madhubala, Rentala (PLOS Neglected Tropical Diseases, 2019)
Author summary The cytochromes P450 (P450s) are ubiquitous heme-containing enzymes that affect a vast range of oxidation reactions in nature. Cytochrome P450s (CYPs) play an essential role in the metabolism of endogenous or xenobiotic compounds and steroid. The sterol compositions among biological kingdoms differ in the specific occurrence of Δ22-sterols. The C22-desaturation reaction is catalyzed by independent cytochrome P450 family proteins, CYP61 in fungi, and CYP710 in plants. Leishmania donovani is a protozoan parasite that causes visceral leishmaniasis (kala-azar). In silico analysis predicted the presence of a plant like CYP710C1 gene in L. donovani that encodes a plant like sterol C-22 desaturase, a key enzyme in stigmasterol biosynthesis. Here, we have characterized CYP710C1 protein of L. donovani. Sterol profile analysis of wild-type, CYP710C1 overexpressing L. donovani and heterozygous mutant parasite showed that CYP710C1 is responsible for stigmasterol production. Amphotericin B has been used in India for treatment of visceral leishmaniasis for over a decade. Our results demonstrated that overexpression of CYP710C1 gene leads to resistance to amphotericin B in L. donovani. Furthermore, characterization of a plant like CYP710C1 gene in Leishmania indicates the presence of a hybrid pathway that shares a resemblance to both fungal and plant pathways.